(untitled) (Orfeu, 2021)
The theme of this study was about creativity in the musical practice of music teachers. The objective was to investigate through qualitative and quantitative design, conceptions about musical creativity, of teachers acting as autonomous teachers or in specific institutions of music teaching, in the city of Curitiba and in nearby regions. The methodology used was a hybrid model that involved a Survey and a Case Study, carried out in two stages (A and B). The results of Stage A, carried out with 71 music teachers, revealed that 99% of the participants believed that the teacher can conduct a creative class and 100% agreed that the student’s musical creativity can be developed. The teachers also presented their own conceptions/opinions about the presence of creativity in the teaching of music, highlighting three main categories: creativity as innovative teaching; as student autonomy; and how to solve problems. Stage B, which had the participation of an instrument teacher, revealed that his practices were in line with the perspective of teaching creativity as problem solving, in addition to demonstrating his creative production in line with studies on multiple approaches to creativity. The results of this study corroborate the research on creativity in teaching music practice, helping to reflect on the need to consider the potential of creative practices to optimize the teaching process.